2013
DOI: 10.1021/nl4011172
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Range Modulation of Light Emission in Two-Dimensional Semiconductors by Molecular Physisorption Gating

Abstract: In the monolayer limit, transition metal dichalcogenides become direct-bandgap, light-emitting semiconductors. The quantum yield of light emission is low and extremely sensitive to the substrate used, while the underlying physics remains elusive. In this work, we report over 100 times modulation of light emission efficiency of these two-dimensional semiconductors by physical adsorption of O2 and/or H2O molecules, while inert gases do not cause such effect. The O2 and/or H2O pressure acts quantitatively as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

55
797
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 731 publications
(861 citation statements)
references
References 26 publications
55
797
8
1
Order By: Relevance
“…Removing such molecules prevents the charge transfer from the MoS 2 layers resulting in an increasing charge carrier density. The binding energies of physisorbed H 2 O and O 2 molecules on the surface of MoS 2 determined from density functional theory (DFT) calculations are 110 meV and 79 meV, respectively [12,14]. Consistently, both molecules can be easily removed with measurements under high-vacuum conditions, especially during the exposure to light.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Removing such molecules prevents the charge transfer from the MoS 2 layers resulting in an increasing charge carrier density. The binding energies of physisorbed H 2 O and O 2 molecules on the surface of MoS 2 determined from density functional theory (DFT) calculations are 110 meV and 79 meV, respectively [12,14]. Consistently, both molecules can be easily removed with measurements under high-vacuum conditions, especially during the exposure to light.…”
mentioning
confidence: 79%
“…It has been reported in literature from photoluminescence measurements that physisorption of H 2 O and O 2 molecules leads to a reduction of the charge carrier density in MoS 2 [12,14].The physisorbed molecules act as molecular gates [12,15] [12,14]. These values are for defect free crystals.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The polymer residues as well as adsorbed H2O and O2 are known to modify the optical and electrical properties of the film, such as the quenching of photo-generated excitons and the reduction of carrier mobility. 5,[23][24][25] Temperature dependent Raman scattering has been used to investigate the vibrational properties of both bulk and monolayer MoS2, and in general both E2g and A1g peaks exhibit redshift with increasing temperature. 2, [26][27][28] Besides the fundamental interest in the vibrational properties of the 2D material, we have shown that because of the expected nearly linear temperature dependence of the phonon frequencies for an idealistic 2D material in the elevated temperature region (above RT), the temperature dependent Raman study can be used as an effective probe to the film-substrate interaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that exposure of 1L-MoS 2 to O 2 and H 2 O gases can lead to drastic PL enhancement. 13 This is because the physically adsorbed molecules can deplete the extra electrons and promote radiative recombination of the excitons and efficient light emission. Meanwhile, it is found that structure defects in 1L-MoS 2 sheet play also an important role for the PL process, 14 though the underlying mechanism remains poorly understood.…”
mentioning
confidence: 99%